Socially Responsible Investment Sukuk: A Systematic Review of the Scientific Literature - Reza Yarmohammadi; Ali Salehabadi; Mohammad Tahidi; Adel Azar (تحقیقات مالی اسلامی (پیوسته))
One of the recent developments in the Islamic securities market is the issuance of Socially Responsible Investment Sukuk (SRI), which focuses on environmental, social and governance (ESG) issues. Despite the dramatic growth of these papers over the past few years, only a handful of studies have addressed this issue. Therefore, the purpose of this study is to systematically review the literature on Islamic securities investment with social responsibility in order to provide comprehensive guidance for future research. A total of 383 articles from the Science and Scopus Network database were selected for analysis of bibliographic studies during the years 2000 to May 2021. The present study shows that the literature of SRI Sukuk is mainly in 10 areas: (1)definition of SRI Sukuk, (2)competitiveness, (3)types, (4)nature of risk and return, (5)terms and characteristics of plans and projects Eligible, (6)Defines strategies for selecting eligible projects, (7)Measures and indicators of effectiveness, (8)Potential actors, (9)Motivational policies and (10)Monitoring and reporting methods. However, there are very few studies on the criteria and indicators of effectiveness and the conditions and characteristics of eligible designs and projects of this type of sukuk. Research also shows that the United States, the United Kingdom, China, Germany, Australia, and Italy have done the most research on socially responsible investment sukuk.